2017
DOI: 10.1021/acschembio.7b00359
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces albus: A New Cell Factory for Non-Canonical Amino Acids Incorporation into Ribosomally Synthesized Natural Products

Abstract: The incorporation of noncanonical amino acids (ncAAs) with different side chains into a peptide is a promising technique for changing the functional properties of that peptide. Of particular interest is the incorporation of ncAAs into peptide-derived natural products to optimize their biophysical properties for medical and industrial applications. Here, we present the first instance of ncAA incorporation into the natural product cinnamycin in streptomycetes using the orthogonal pyrrolysyl-tRNA synthetase/tRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 53 publications
2
32
0
1
Order By: Relevance
“…S4). This is consistent with previous work which reported that deoxy versions of lantibiotics have lower biological activity (43).…”
Section: Resultssupporting
confidence: 94%
“…S4). This is consistent with previous work which reported that deoxy versions of lantibiotics have lower biological activity (43).…”
Section: Resultssupporting
confidence: 94%
“…The high substrate tolerance of the NisBTC system allows modification not only of RiPPs from different origins ( van Heel et al, 2016 ), but also of the newly synthesized nisin(BocK) variants. With our results for L. lactis and previous works on B. cereus ( Luo et al, 2016 ) and Streptomyces albus ( Lopatniuk et al, 2017 ), SCS has now been successfully implemented in three Gram-positive organisms from different prokaryotic families. In all three cases, expression of an OTS was successfully combined with the natural PTM enzymes for either nisin (current study), thiocillin ( Luo et al, 2016 ), or cinnamycin ( Lopatniuk et al, 2017 ) of the expression host.…”
Section: Discussionmentioning
confidence: 60%
“…For example, incorporation of ncAAs at discrete positions on Nisin expanded building blocks that can be biosynthetically incorporated into lanthipeptide and diversified macrocyclic topologies of this antibacterial peptide [ 100 ]. Likewise ncAAs have been successfully introduced into other lanthipeptides [ 101 , 102 ], lasso peptides [ 103 , 104 ], macrocyclic peptides [ 105 ], thiopeptides [ 106 ] as well as in the natural product cinnamycin, recently [ 107 ].…”
Section: Biosynthesized Therapeutic Peptidesmentioning
confidence: 99%